2016
DOI: 10.1111/gtc.12328
|View full text |Cite
|
Sign up to set email alerts
|

Eomesodermin promotes interferon‐γ expression and binds to multiple conserved noncoding sequences across the Ifng locus in mouse thymoma cell lines

Abstract: The T-box transcription factors T-bet and eomesodermin (Eomes) have been shown to regulate the lineage-specific expression of interferon-c (IFN-c). However, in contrast to T-bet, the role of Eomes in the expression of IFN-c remains unclear. In this study, we investigated the Eomes-dependent expression of IFN-c in the mouse thymoma BW5147 and EL4 cells, which do not express T-bet or Eomes. The ectopic expression of Eomes induced BW5147 and EL4 cells to produce IFN-c in response to phorbol 12-myristate 13-acetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
3
13
0
Order By: Relevance
“…Our data indicate that IFN-γ production by Tc REG is controlled by NF-κB signaling. Based on our data and published studies (52, 63, 64), we interpret these results to indicate that NF-κB contributes (or regulates) to the expression of T-bet and Eomes in Tc REG , which then leads to IFN-γ production (Fig. 5D).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our data indicate that IFN-γ production by Tc REG is controlled by NF-κB signaling. Based on our data and published studies (52, 63, 64), we interpret these results to indicate that NF-κB contributes (or regulates) to the expression of T-bet and Eomes in Tc REG , which then leads to IFN-γ production (Fig. 5D).…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported previously that T-bet and Eomes bind to distal conserved non-coding sequences (CNS) to regulate histone modification and expression of IFN-γ gene (5052). Consistent with these results, we found that in Tc REG cells T-bet and Eomes bind to CNS located at −22K and −34K from IFN-γ gene transcription start (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then transfected EL-4 mouse lymphoma cells with a luciferase reporter system containing a 2 kb Tox promoter region and determined whether T-bet repressed Tox transcription directly. EL-4 cells lack endogenous expression of T-bet and Eomes (Fukuoka et al, 2016), and retrovirally delivered T-bet but not Eomes reduced the activity of the Tox reporter construct by 50%–60% (Figure 3F). Furthermore, we analyzed LCMV-OVA-primed OT-1 cells by T-bet chromatin immunoprecipitation analysis followed by PCR (ChIP-PCR) of various Tox promoter regions.…”
Section: Resultsmentioning
confidence: 99%
“…DNA was purified by Qiagen PCR purification kit and used as template for PCR amplification with specific primers flanking the T-bet binding sites in CNS enhancer regions of the Ifng locus as defined previously (18, 19). The primers (20) used are listed below:…”
Section: Methodsmentioning
confidence: 99%